The Golden Fly Series - Margreiter, A. (New Studies in Athletics, 2015)
Designed to address the challenge of raising the profile of athletics again, the Golden Fly Series is the world's first-ever international city centre athletics tour. The concept sees athletes compete in the long jump and pole vault on the world`s largest mobile track and field apparatus, the FlySwat - which has been developed specifically for the series - set up in iconic city centre venues. Spectators are close to the action so they con feel the emotions of each attempt. Series events also include activities to introduce children and young people to athletics and educate them about a healthy lifestyle. The response to the first year of the tour (2013) was positive with large crowds witnessing the competitions in four cities and significant coverage in the media. This case study, written by the creator of the series, describes the concept, covering the background, aims, technical information, marketing activities and an evaluation of the first year. He concludes by stating the concept can work and that the organisers are constantly seeking ways to develop it and extend its boundaries.